2009
DOI: 10.1074/jbc.m109.013862
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TLR2 Protein Expression by miR-105 in Human Oral Keratinocytes

Abstract: Mammalian biological processes such as inflammation, involve regulation of hundreds of genes controlling onset and termination. MicroRNAs (miRNAs) can translationally repress target mRNAs and regulate innate immune responses. Our model system comprised primary human keratinocytes, which exhibited robust differences in inflammatory cytokine production (interleukin-6 and tumor necrosis factor-␣) following specific Toll-like receptor 2 and 4 (TLR-2/TLR-4) agonist challenge. We challenged these primary cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 53 publications
1
109
0
1
Order By: Relevance
“…Furthermore, miR-147 attenuates the TLR-induced inflammatory response in macrophages . In another study, miR-105 was shown to modulate TLR-2 translation in human gingival keratinocytes (Benakanakere et al, 2009). It was recently suggested that the TLR4-dependent reprogramming of inflammatory genes is mediated by two distinct levels of regulation .…”
Section: Micrornas and Inflammationmentioning
confidence: 99%
“…Furthermore, miR-147 attenuates the TLR-induced inflammatory response in macrophages . In another study, miR-105 was shown to modulate TLR-2 translation in human gingival keratinocytes (Benakanakere et al, 2009). It was recently suggested that the TLR4-dependent reprogramming of inflammatory genes is mediated by two distinct levels of regulation .…”
Section: Micrornas and Inflammationmentioning
confidence: 99%
“…A reciprocal relationship between TLR2 signaling and miR-105 was found in primary human oral keratinocytes, and TLR2 mRNA was shown to be regulated by miR-105. 75 However, in fibroblast-like synoviocytes from rheumatoid arthritis patients, miR-19a/b was decreased in response to TLR2 ligands and was responsible for the upregulated TLR2 expression in these cells. 76 miR-19a/b mimics reduced TLR2 level and thus inhibited TLR2-triggered cytokine production.…”
Section: Introductionmentioning
confidence: 97%
“…64 In oral keratinocytes, miR-105 regulates TLR2. 65 In mouse peritoneal macrophages, Let-7 family miRNAs target TLR4. 50 Downstream of the TLRs, miR-145 and miR-146a target the TLR adapter proteins TRAF6 and IRAK1.…”
Section: Spotlightmentioning
confidence: 99%